COMPARATIVE ANALYSIS OF INDIGENOUS BACTERIAL AND FUNGAL CONSORTIA FOR ENHANCED CHROMIUM DETOXIFICATION AND ENVIRONMENTAL SAFETY - Manasi Maroti Borkar (The Bioscan, 2026)
The research concentrates on the development and characterization of mixed bacterial–fungal consortia derived from industrial effluents and contaminated soils for the biodegradation and detoxification of hexavalent chromium [Cr(VI)]. This study examines the synergistic interactions between indigenous bacteria (Bacillus subtilis, Lysinibacillus macroides) and filamentous fungi (Aspergillus niger, Penicillium chrysogenum), in contrast to previous studies that focused solely on bacterial communities. The detoxification efficiency, assessed at 50, 100, and 200 mg/L Cr(VI), demonstrated a removal rate of up to 87% within 72 hours under optimized conditions (pH 7, temperature 35°C). The results show that microbial synergism is a long-term and cost-effective way to get rid of heavy metals with little risk to the environment. Keywords Chromium detoxification, microbial consortium, Bacillus subtilis, Aspergillus niger, synergistic bioremediation, environmental safety.